DETERMINANTS OF GOJEK CUSTOMER SATISFACTION: ELECTRONIC SERVICE QUALITY, TRUST, AND PERCEIVED VALUE (A CASE STUDY ON GOJEK USERS IN PEKALONGAN) - Emilia Dwi Lestari; Farida Rohmah (Islamic Economic and Business Journal, 2026)
This study aims to determine the effect of electronic service quality, trust, and perceived value on Gojek customer satisfaction in Pekalongan among students of Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan. This research employs a quantitative approach with data collected through questionnaires. A sample of 97 respondents was selected using purposive sampling technique. The data were analyzed using multiple linear regression with IBM SPSS 27. The results show that partially, electronic service quality has no significant effect on customer satisfaction, while trust and perceived value each have a positive and significant effect on customer satisfaction. Simultaneously, all three independent variables together have a significant effect on customer satisfaction of Gojek transportation mode in Pekalongan among students of Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan.